New Nine Coordinated Hydrated Heavier Lanthanide Ethylenediaminetetraacetates Containing Hydrazinium Cation: Molecular Structure of N2H5[Tb(EDTA)(H2O)3]·5H2O and N2H5[Gd(EDTA)(H2O)3]·5H2O - Vikram, L.; Sonia, C.; Sivasankar, B.N. (Asian Journal of Chemistry, 2012)
Two complexes of lanthanide with the composition N2H5[Tb(III)(EDTA)(H2O)3]·5H2O (I) and N2H5[Gd(III)(EDTA)(H2O)3]·5H2O (II) (EDTA = ethylenediaminetetraacetic acid) were prepared and characterized by X-ray single crystal diffraction technique. For I and II the Tb(III) and Gd(III) ions are nine coordinated by an EDTA ligand and three coordination water molecules, yielding a monocapped square-antiprisamatic (MCSAP) conformation. Complexes I and II are crystallizes in the orthorhombic system with Fd22 space group. The crystal data are as follows: a = 19.5030(9), b = 35.3459(17), c = 12.2825(5), a = b = g = 90, V = 8467(7) Å3, Z = 16, r = 1.704 Mg/m3, μ = 3.405 mm-1, F(000) = 4208, R1 = 0.0390 and wR2 = 0.1101 for 22995 observed reflections with I ³ 2s(I). The crystal data of the complex II are as follows: a = 19.5336(7) Å, b = 35.3788(14) Å, c = 12.2792(5) Å, a = b = g = 90º, V = 8485.9(6), Z = 16, r = 1.745 Mg/m3, μ = 3.196 mm-1, F(000) = 4320, R1 = 0.0226 and wR2 = 0.0666 for 8558 observed reflections with I = 2s(I). According to thermal analyses, the collapsing temperatures of crystal structure are 260 ºC for I and 240 ºC for II, which indicate that the crystal structure of I is more stable.